Improvement of Metacognitive Thinking Skills in Teacher-Student Scientific Assignments Through the Use of Online Platforms - Hermawan, Cecep Maman; Rosfiani, Okta; Abrar-ul-Hassan, Shahid; Kuswiyanti, Tanti Sri; Sudin, Mahmudin; Roswati, Siti (TARBIYA: Journal of Education in Muslim Society, 2022)
AbstractScientific problem-solving, starting with simple tasks and growing in difficulty until reaching the task with the climax level of difficulty, can be used as a training tool for developing metacognitive thinking abilities. Teachers and lecturers can make the most of scaffolding from online platforms by demonstrating how to complete a task in a systematic way. This study uses a participatory action research/PAR design with a class of students from the Islamic Religious Education study program at the University of Muhammadiyah Jakarta to examine how students learn metacognitive thinking abilities from completing scientific assignments in research methods courses employing interviews, documents, and observation to gather data. One of the study's most significant findings is that lecturers can use a number of strategies to help students develop their metacognitive thinking skills. These strategies are as follows: 1) Students can be trained in learning metacognitive thinking skills as early as the first semester through English resources introduced by lecturers from reputable online search engines; 2) Lecturers can offer a focus on research methodology assignments that require students to access various online platforms in their work; 3) It is recommended that research methodology courses be spread out in the early, middle, and final semesters; 4) Lecturers can improve the metacognitive thinking skills and self-efficacy of more advanced students by using various approaches, strategies and learning resources. If necessary, a reward and punishment system can be applied, especially to motivate male students and students who lack discipline.AbstrakPemecahan masalah ilmiah, mulai dari tugas-tugas sederhana dan berkembang dalam tingkat kesulitan hingga mencapai tugas dengan tingkat kesulitan klimaks, dapat digunakan sebagai sarana latihan untuk mengembangkan kemampuan berpikir metakognitif. Guru dan dosen dapat memanfaatkan scaffolding dari platform online dengan mendemonstrasikan cara menyelesaikan tugas secara sistematis. Penelitian ini menggunakan desain penelitian tindakan/PAR partisipatif dengan melibatkan sekelompok mahasiswa program studi Pendidikan Agama Islam Universitas Muhammadiyah Jakarta untuk mengkaji bagaimana mahasiswa mempelajari kemampuan berpikir metakognitif dari menyelesaikan tugas ilmiah dalam mata kuliah metode penelitian dengan menggunakan wawancara, dokumen, dan observasi untuk mengumpulkan data. Salah satu temuan studi yang paling signifikan adalah bahwa dosen dapat menggunakan sejumlah strategi untuk membantu mahasiswa mengembangkan kemampuan berpikir metakognitif mereka. Strategi-strategi tersebut adalah sebagai berikut: 1) Mahasiswa dapat dilatih untuk mempelajari keterampilan berpikir metakognitif sejak semester pertama melalui sumber bahasa Inggris yang diperkenalkan oleh dosen dari mesin pencari online; 2) Dosen menawarkan fokus pada tugas metodologi penelitian yang mengharuskan mahasiswa untuk mengakses berbagai platform online dalam pekerjaannya; 3) Disarankan mata kuliah metodologi penelitian disebarluaskan pada semester awal, tengah, dan akhir; 4) Dosen dapat meningkatkan kemampuan berpikir metakognitif dan efikasi diri mahasiswa yang lebih maju dengan menggunakan berbagai pendekatan, strategi dan sumber belajar. Jika perlu dapat diterapkan sistem reward and punishment terutama untuk memotivasi siswa laki-laki dan siswa yang kurang disiplin. How to Cite : Hermawan, C. M., Rosfiani, O., Hassan, S. A, Kuswiyanti, T. S., Sudin, M., Roswati, S. (2022). Improvement of Metacognitive Thinking Skills in Teacher-Student Scientific Assignments Through the Use of Online Platforms. TARBIYA: Journal of Education in Muslim Society, 9(2), 190-197. doi:10.15408/tjems.v9i2. 30818.